Formas de controle e individualização do preso: uma via possível para compreensão do exame criminológico nas Penitenciárias I e II de Foz do Iguaçu - Friedrich, Luciane Neitzel (2014)
The object of this dissertation is the Criminological Examination, prepared by Social Service and Psychology professionals, as an aid to the decision of the Judge of the Criminal Enforcement of Foz do Iguaçu/PR regarding the progression of regime of prisoners from Foz do Iguacu state penitentiaries (Foz do Iguaçu State Penitentiary I and Foz do Iguaçu State Penitentiary II) in 2012. This dissertation aims to understand the purpose of criminological examination. Thus, it seeks to discuss the criminological examination, its legal and theoretical reasoning as well as its merits, taking into account a set of overlapping correlations involved in its execution, which encompasses different specialized knowledge such as the knowledge of psychologists, social workers, Judges of Criminal Enforcement and Public Prosecutors. The argument explored is the conducting methods, the goals and the power relations between different actors involved in the preparation of this exam, intrinsic to the judicial practices of a disciplinary society in which we seek social control and appropriateness of behaviors. It is observed that by individualizing the service and elaborating the criminological examination, there is a construction of the individual s identity as a prisoner within the penal system, thus resulting in the blaming of the individual and his family for criminal involvement, and making him liable for his process of reintegration into society. The family is seen in this context as an important link between the prisoner and society during the execution of the sentence, and source of support for his return to social life.